PHYLOGENETIC RELATIONSHIP BETWEEN FOUR SPECIES USING DIVERGENT DOMAIN D8 IN FAMILY: SILURIDAE: Life Science-Zoology - VERMA, JYOTI; M. SERAJUDDIN (International Journal of Life Science and Pharma Research, 2012)
Molecular characterization and assessment of genetic variation in 28S region especially divergent domain D8 ribosomal DNA in fresh water catfish Ompok pabda, O. pabo, O. bimaculatus and W. attu was carried. The nucleotide sequences and GC% of divergent domain of 28S ranged from 302-473 bp and 54% in all above subject species. It was found that the genetic distance between O. pabda and W. attu was highest, followed by O. bimaculatus and W. attu in the pair wise comparison. Since the genetic identity between O. pabda and O. pabo was highest, it can be said that these two species were most closely related as compared to the other species combinations. DNA sequence data play an essential role in the reconstruction of evolutionary relationships among the organisms, resulting in insights in genetic affinities that may confirm or conflict with traditional taxonomy because of attractive properties, the rDNA is popular for examine phylogenetic relationships and for studying genetic variability and divergence within and between species. The sequence alignment suggested the presence of insertions/ deletions (indels) and substitutions (transitions and transversions) in these regions. The indels were responsible for length variations. The study suggested that Ompok species has a closer relationship forming one cluster, in which O. pabo and O. pabda were closely related as compared to O. bimaculatus. The species W. attu radiated far and formed separate cluster.